(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to investigate the frequency at which physicians test hepatitis B virus (HBV) serology before treatment and the rate of hepatitis B virus reactivation (HBVr) after treatment in patients undergoing chemotherapy (CT) due to a solid organ malignancy (SOM) or hematological malignancy (HM). Materials and Methods: Baseline clinical feature, HBV serology, and liver function test data for 1275 patients ≥ 18 years of age who underwent CT for the first time due to various SOMs and HMs from 2015-2017 were obtained from the database and retrospectively analyzed. HBV serology was studied in 296 (201 HM, 95 SOM) of the 1275 patients retrieved from the database. Results: The prevalence of HBV was 9.5% (121 patients). Only 49 (40.4%) HBV-positive patients had HBV DNA. Of those, 72 (59.5%) underwent prophylactic antiviral therapy. HBVr was detected in only 3 patients (1.5%), and all of those patients had HMs and were recommended oral antiviral therapy but did not. Conclusion: In patients with SOMs, the screening rates of HBV serology, as well as prophylaxis and follow-up HMs were extremely low. Therefore, these patients should be screened for HBV serology and prophylactic treatment should be given when necessary for HBVr.